Effects of biochar and vermicompost on microorganisms and enzymatic activities in greenhouse soil - Wu, Qianqian; Zhang, Jie; Liu, Xinna; Chang, Tingting; Wang, Qian; Shaghaleh, Hiba; Hamoud, Yousef Alhaj (Frontiers in Environmental Science, 2023)
The effects of different contents of biochar and vermicompost on the microbial and enzymatic activities of greenhouse soil were determined to provide a theoretical basis for improving the quality of greenhouse soil. The experiment was conducted in a greenhouse using potted tomatoes. Five treatments consisted of different content ratios of organic amendments: 1% biochar (BC1), 3% biochar (BC3), 5% biochar (BC5), 3% vermicompost (VC3), and 5% vermicompost (VC5), with no addition of organic amendments as the control (CK). Compared with CK, the pH, organic matter content, and DOC concentration increased in treatment groups. The organic matter content of BC3 and BC5 significantly increased by 54.6% and 72.8%, respectively, and DOC concentration of BC3 significantly increased by 43.9%. Biochar and vermicompost significantly increased the diversity of bacterial and fungal communities in soil, as well as the abundance of Actinomycetes, Acidobacteria, Ascomycetes, and Aspergillus, and reduced the abundance of Aspergillus. The activities of urease and alkaline phosphatase were significantly increased, and the activity of nitrate reductase was inhibited in all treatment groups compared with CK. In addition, a highly significant positive correlation was observed among pH, Acidobacteria phylum abundance, and alkaline phosphatase activity in all treatments. DOC concentration was positively correlated with pH, organic matter content, Acidobacteria phylum abundance and alkaline phosphatase activity. Biochar and vermicompost were effective in improving the physicochemical properties of greenhouse soil, enhancing microbial diversity, and affecting enzymatic activities. Therefore, the effect of BC3 (3% biochar) on community diversity and alkaline phosphatase and nitrate reductase activities reaches a threshold. This study highlights that biochar and vermicompost as organic amendments are recommended to improve the quality of greenhouse soils.